Organic azido compounds as energetic materials - Künzel, Martin; Jalový, Zdeněk; Zigmund, Jan (University of Pardubice, 2011)
Azido compounds suitable for propellants are described with respect to their particular application as energetic materials. General synthetic methods are briefly described. Physical properties, sensitivity and thermal stability characteristics of the compounds are summarized.